Between the Fact and the Guess. Expression of a Real Reserve on Information Portals - Mazurkiewicz-Sułkowska, Julia (W kręgu zagadnień języka, literatury i kultury: Księga jubileuszowa dedykowana Profesorowi Jarosławowi Wierzbińskiemu, 2022)
The tendency to mark the truth’s reserve in the mass media, especially in electronic media, has been one of the qualities of the language of the press in recent years. This is seen both in the languages with a morphologized imperceptive modality (re-narration + truth’s reserve), and in the languages that do not have separate grammatical categories to stipulate truthfulness. Speaking of Slavic languages, the first of these types can be traced to the Bulgarian language. The Bulgarian linguists were the first to draw attention to the expansion of the so-called inferential mood in the mass media. The analysis of web portals shows that the need to shift responsibility for the accuracy of the information provided is equally widespread in Polish, which uses lexical exponents and paramorphological constructions for the same purpose.